Cross-Cultural Adjustment of Asian International Graduate Students in the United States: Theorizing from the Literature - Buasawan Simmala (Adult Education Research Conference, 2008)
The flow of graduate students from Asia to the U.S. has become a fundamental phenomenon; however, understanding their adjustment difficulties to the host culture and academic system is limited. Drawing from the literature, this paper seeks to increase understanding of these students’ needs through theorizing about their cross-cultural adjustments.